Cult books revisited: John Hick's God and the Universe of Faiths - Barnes, Philip (Theology, 2019)
This article provides an account of John Hick's first expression of his pluralist theology of religions as he presented it in God and the Universe of Faiths (1973). Attention is focused on the reasons that he believes justify regarding the different religions as independent sources of revelation and salvation and on their assessment.